We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
61
2
avatar

1.https://prnt.sc/mr2wq7

2.https://prnt.sc/mr2xr8

 Feb 28, 2019
 #1
avatar+100546 
0

1. 

 

x^2 + 5x - 6             ( x + 6)( x - 1)

__________  =       ___________

x^2 - x - 6                (x - 3) ( x + 2)

 

We will have zeros at x = -6 and x = 1

We will have a y intercept of (0, 1)

We will have vertical asymptotes at  x = 3 and x = -2

 

The graph on the bottom left is correct....

 

 

cool cool cool

 Feb 28, 2019
 #2
avatar+100546 
+1

2.

 

x^2 - x - 2  =

 

(x  - 2) ( x + 1)

 

We have zeros at x  = 2  and x = -1

 

The only graph where this is true is the one at the top left

 

cool cool cool

 Feb 28, 2019

8 Online Users

avatar